Law Enforcement on By-Pass Water Theft at PDAM Palangka Raya - David, Kristian; Farina, Thea; Sangalang, Rizki Setyobowo (Journal of Law, Politic and Humanities, 2025)
Water theft through by-pass on PDAM installations is one of the criminal acts that harm local companies and negatively impact the quality and quantity of clean water distribution. This research aims to analyze law enforcement against the crime of water theft in the PDAM of Palangka Raya City, identify the modus operandi used by the perpetrators, and examine the resulting impacts. The research employs empirical legal methods with a qualitative approach, where data is obtained through field observations, documentation, and interviews with relevant parties. The research findings indicate that the modus of theft is carried out by illegal connections on the distribution pipes before the water meter, so the usage is not recorded and the bill does not appear. This action violates Article 362 and Article 363 of the Indonesian Penal Code, Article 406 of the Penal Code, as well as Article 55 paragraph (1) in conjunction with Article 73 paragraph (1) of Law Number 17 of 2019 concerning Water Resources. Water theft results in financial losses for PDAM. decreased water pressure, service disruptions, and potential contamination. Strict law enforcement and increased legal awareness in the community are needed to prevent the recurrence of these criminal acts.